Global Impact and Management in Patients with Senile Osteoporosis: A Systematic Review (Asian Journal of Pharmaceutics (AJP), 2025)
Senile osteoporosis is a global health concern characterized by reduced bone density, deteriorated bonemicroarchitecture, and increased fracture risk, particularly in aging populations. This systematic review aimedto evaluate the global impact, risk factors, diagnostic methods, and current gaps in the management of senileosteoporosis. A literature search was performed using PubMed, Scopus, and Web of Science to identify relevantpeer-reviewed articles published in English from 2014 to 2024. The findings were organized thematicallyto match the review objectives. The global prevalence of low bone mineral density and related fractures hasincreased, with mortality and disability – adjusted life years rising by 111.16% and 93.82%, respectively, from1990 to 2019. Women have incidence rates 1.5 times higher than men, and social deprivation contributes to therisk of osteoporosis. Despite its high prevalence, many high-risk individuals, particularly men, do not receiveosteoporosis medication. Age is a critical factor in fracture risk, and a 5-year composite fracture prediction modelfor age-related sites offers superior discrimination compared to other models. This review highlights the need forbetter prevention, early detection, and management strategies, particularly in areas with a high sociodemographicindex and among inadequately treated populations. Expanding fracture liaison services, community screenings,and hospital evaluations can facilitate accurate diagnosis and timely referral. Future research should refinepredictive models, validate risk markers, and incorporate genetic, lifestyle, and environmental factors intoprevention strategies. International cooperation and fair health-care distribution are crucial for reducing the globalimpact of osteoporosis.